Why clinical neuropsychology matters in schizophrenia care - Øie, Merete Glenne; Barbosa, Fernando; Lettner, Sandra; Baker, Gus; Duarte, Cedric; Hessen, Erik; Ueland, Torill (Frontiers in Psychology, 2025)
Cognitive impairments in schizophrenia are widespread, persistent throughout the illness course, and significantly impact quality of life and functional outcomes. Integrating neuropsychological evaluations into routine clinical care is essential for early identification of cognitive impairments. This approach facilitates the implementation of personalized treatment strategies, including tailored neuropsychological rehabilitation, to promote functional recovery. Although recommended by national and international guidelines, many individuals with schizophrenia do not receive neuropsychological assessment. This article emphasizes the integral role of clinical neuropsychology in schizophrenia care, focusing on six key areas: (1) cognitive domains to assess; (2) addressing subjective cognitive complaints; (3) the impact of symptoms, medication, and substance use on cognitive function; (4) test administration and evaluation procedures; (5) the utilization of neuropsychological results and feedback; and (6) the design and implementation of individualized neuropsychological rehabilitation.